EDUCATIONAL MIGRATION IN THE NORTH CAUCASUS: CAUSES, GEOGRAPHY AND POSSIBLE PROBLEMS - Vasily Vasilievich Chihichin (Наука. Инновации. Технологии)
The article analyzes the socio-economic causes of educational migration in the North Caucasus, reveals the geography of the entry and exit of students, and also indicated the problems associated with migration of the North Caucasian youth.